PENEGAKAN HUKUM PIDANA TERHADAP PENGGUNA NARKOBA DI POLDA JATENG - Indah Lestari; Sri Endah Wahyuningsih (Jurnal Hukum Khaira Ummah, 2019)
In overcoming the enforcement of Criminal Law Against Drug Users In Central Java Police. The problems studied are: Criminal law policy contained in the Narcotics Act and Psychotropic Act in the prevention of narcotics and psychotropic crime, Law enforcement against the perpetrators of narcotic crime and psychotropic in Central Java Police, Efforts to overcome drug crime in Central Java Police. know and analyze the criminal law policy as well as the perpetrators as stated in Narcotics Law and Psychotropic Law in Central Java Regional Police. The results of a trial or conspiracy to commit Narcotics and Narcotics Precursor as stipulated in the narcotics law with the same imprisonment as a person committing a crime or violation of the provisions of this narcotic law, for example an experiment to provide narcotics class 1, shall be subject to imprisonment of a minimum of 4 (four) years and a maximum of 12 (twelve) years and a fine of at least Rp800.000.000,00 (eight hundred million rupiah) and a maximum of Rp8,000,000,000.00 (eight billion rupiah ). While law enforcement with non-penal efforts focus more on preventive properties (prevention / penangkalan / penegindalian) before the crime occurred. Given that non-penal crime prevention efforts are more of a preventive measure for the occurrence of crime, the main target is the conducive factors causing the crime. The effort of prevention, Police of Central Java, includes: Prevention efforts, prevention efforts and obstacles faced by Central Java Police According to AKBP Sunarto, SH that efforts to overcome narcotics abuse have obstacles and obstacles in the rehabilitation of drug addicts where there is no place that can accommodate victims of narcotics abuse to do rehabilitation in the city of Semarang.Keywords: Law Enforcement, Drug Users